Raw Material Sustainability And The Performance Of Beverage Companies In Nigeria: A Study Of Intafact Beverages Onitsha - Ndubuisi, Peter Ositadinma; Joy, Nonyelum Ugwu; Udeze, Chimeziem (Archives of Business Research, 2018)
This study examined the Effect of Raw Material Resource Sustainability on the Viability of Organizations. The study adopted survey research approach in its design and covered a population of 236 members of staff while its sample size was 182 members of staff. The data used in this study were generated from both primary and secondary sources. The Spearman rank correlation coefficient (r) was used to calculate the reliability index which yielded a 94% output. The statistical tools used for data analysis were simple percentage (%) and Pearson Product Moment Correlation (PPMC) using the 20.0 version of statistical package for social sciences (SPSS). The study analyzed empirical data generated from a well structured valid and consistent questionnaire and posited that the viability of manufacturing organizations especially those in the beverage industry is significantly influenced by raw material resource sustainability. Moreover, the strength of the effect of raw material resource sustainability appears to be felt more on financial viability and less on management model viability. It was recommended among others that Organizations that must be viable must consciously develop sustainable raw material resources that will facilitate through backward integration cost and time efficiency in their raw material resource value chain, which is a significant impetus for the financial viability of organizations and that integrating the value chain of the organization can enhance the sustainability of raw material resource of manufacturing firms.